Method for producing carbon nanotube molded body and carbon nanotube molded body
A novel method for producing carbon nanotube molded bodies with high density and large specific surface area addresses the limitations of existing methods, resulting in improved mechanical and electrical properties.
Patent Information
- Application Number
- JP2021018825
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-02-09
- Publication Date
- 2025-01-07
- Estimated Expiration
- 2041-02-09
AI Technical Summary
Existing methods for producing carbon nanotube sheets result in low density and small specific surface area due to impurities and agglomeration, making it difficult to achieve high performance properties.
A method involving the use of a carbon nanotube dispersion containing carbon nanotubes, cellulose nanofibers, monosaccharides, and a dispersion medium, followed by heating, drying, and firing to produce a carbon nanotube molded body with high density and large specific surface area.
The method enables the production of carbon nanotube molded bodies with densities of 0.55 g/cm³ or more and specific surface areas of 500 m²/g or more, enhancing mechanical strength and electrical conductivity.
Smart Images

Figure 0007608691000002 
Figure 0007608691000003 
Figure 0007608691000004
Abstract
Description
[Technical field]
[0001] The present invention relates to a method for producing a carbon nanotube molded article and a carbon nanotube molded article. [Background technology]
[0002] In recent years, carbon nanotubes (hereinafter sometimes referred to as "CNTs") have attracted attention due to their excellent properties such as high electrical conductivity, excellent thermal conductivity, and large specific surface area. Currently, it has been proposed to mold CNTs into various shapes and use them in various products such as electrodes. For example, CNT molded bodies such as CNT sheets are mainly formed using the chemical vapor deposition method (CVD method) (for example, see Non-Patent Document 1). [Prior art documents] [Non-patent literature]
[0003] [Non-Patent Document 1] Jacob W. Singleton and 2 others, "Relationships between tensile behavior, physical parameters and manufacturing parameters of carbon nanotube sheet", Materials and Design, vol.116, p.199-206 Summary of the Invention [Problem to be solved by the invention]
[0004] However, the above-mentioned properties of CNTs are the properties of individual nano-scale CNTs, and there are many challenges to overcome in order to make these properties manifest in molded products such as CNT sheets. For example, when a CNT sheet is formed using the CVD method, the density is low and the specific surface area is small. This is because the CNT sheet contains a lot of impurities and the CNTs are in a highly aggregated state. For this reason, it is currently not possible to obtain a CNT sheet that has both a high density and a large specific surface area.
[0005] The present invention has been made to solve the above problems, and an object of the present invention is to provide a method for producing a carbon nanotube molded body having a high density and a large specific surface area, and to provide a carbon nanotube molded body. [Means for solving the problem]
[0006] [1] A method for producing a carbon nanotube molded product containing carbon nanotubes, the method comprising the steps of obtaining a carbon nanotube dispersion containing carbon nanotubes, cellulose nanofibers, monosaccharides, and a dispersion medium; supplying the carbon nanotube dispersion into a mold and drying it to obtain a solidified product of the carbon nanotube dispersion; and firing the solidified product to carbonize the cellulose nanofibers, wherein the step of obtaining the carbon nanotube dispersion comprises a step of heating the dispersion containing the carbon nanotubes, the cellulose nanofibers, the monosaccharides, and the dispersion medium to a temperature of 120°C or higher and 180°C or lower, or a step of heating a first dispersion containing the cellulose nanofibers and the monosaccharides to a temperature of 120°C or higher and 180°C or lower, and then mixing the first dispersion with a second dispersion containing the carbon nanotubes and the dispersion medium, wherein the ratio of the mass of the monosaccharides to the mass of the cellulose nanofibers in the dispersion or in the first dispersion before the heating is 100 or more.
[0007] [2] The method for producing a composition according to the above item [1], wherein the heating to the aforementioned temperature is carried out under a pressure of 0.2 MPa or more and 10 MPa or less.
[0008] [3] A carbon nanotube molding containing carbon nanotubes, the density of the carbon nanotube molding being 0.55 g / cm 3 or more, and the specific surface area of the carbon nanotube molded body is 500 m 2 / g or more.
[0009] [4] The carbon nanotube molded body according to the above [3], wherein the carbon content in the carbon nanotube molded body is 55 mass % or more.
[0010] [5] The carbon nanotube molded body according to the above [3] or [4], which is a carbon nanotube sheet. Effect of the Invention
[0011] According to the method for producing a carbon nanotube molded body and the carbon nanotube molded body of the present invention, it is possible to obtain a carbon nanotube molded body having a high density and a large specific surface area. [Brief description of the drawings]
[0012] [Figure 1] 1(A) to 1(C) are diagrams that diagrammatically show the steps of producing a carbon nanotube molded article according to an embodiment. [Diagram 2] 2(A) to 2(C) are diagrams that diagrammatically show the steps of producing a carbon nanotube molded article according to the embodiment. [Diagram 3] FIG. 3 is a scanning electron microscope photograph of the carbon nanotube molded article according to Example 1. As shown in FIG. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0013] Hereinafter, a carbon nanotube molded body and a manufacturing method thereof according to an embodiment of the present invention will be described with reference to the drawings. Figures 1(A) to 1(C) and 2(A) to 2(C) are diagrams that typically show the manufacturing process of a carbon nanotube molded body according to an embodiment.
[0014] <<<Method of manufacturing carbon nanotube molded body>>> First, a carbon nanotube dispersion is obtained. The carbon nanotube dispersion contains carbon nanotubes, a dispersion medium, a dispersant, cellulose nanofibers (hereinafter sometimes referred to as "CNF"), and monosaccharides. Note that the carbon nanotube dispersion preferably contains a dispersant, but it does not have to contain a dispersant as long as it contains carbon nanotubes, a dispersion medium, cellulose nanofibers, and monosaccharides. Note that the carbon nanotube dispersion may contain impurities (e.g., catalysts and amorphous carbon) derived from the process in the production of carbon nanotubes.
[0015] <Carbon nanotubes> The carbon nanotubes may be either single-walled or multi-walled. When the carbon nanotubes are single-walled, they have excellent electrical and thermal conductivity, and therefore the carbon nanotube molded product has high performance. When the carbon nanotubes are multi-walled, they are superior in terms of cost.
[0016] The diameter of the carbon nanotube is preferably 0.7 nm or more and 80 nm or less. The diameter of the carbon nanotube can be measured using a transmission electron microscope (TEM), and the diameter of 10 carbon nanotubes is measured and the arithmetic average value is defined as the diameter of the carbon nanotube.
[0017] The length of the carbon nanotube is preferably 1 μm or more and 100,000 μm or less. If the length of the carbon nanotube is 1 μm or more, it is easy to form a molded body such as a sheet, and if the length is 100,000 μm or less, it is easy to disperse the carbon nanotube. From the viewpoint of forming a structure, the lower limit of the length of the carbon nanotube is preferably 2 μm or more, 5 μm or more, or 10 μm or more, and from the viewpoint of the difficulty of the dispersion treatment, the upper limit is preferably 50,000 μm or less, 10,000 μm or less, or 100 μm or less. The length of the carbon nanotube can be measured using an atomic force microscope (AFM), and the length of 10 carbon nanotubes is actually measured, and the arithmetic average value is taken as the length of the carbon nanotube.
[0018] The ratio of the length of the carbon nanotube to the diameter of the carbon nanotube (length / diameter, aspect ratio) is preferably 1000 or more and 1,000,000 or less. If the aspect ratio is 1000 or more, the formation of a structure becomes easy, and if it is 1,000,000 or less, the dispersion treatment of the carbon nanotube becomes easy. The lower limit of the aspect ratio is preferably 2000 or more, 3000 or more, or 5000 or more, and the upper limit is preferably 500,000 or less, 100,000 or less, or 10,000 or less.
[0019] <Dispersion medium> Examples of the dispersion medium include water, a water-soluble organic solvent, and a mixture thereof. Among these, water is preferred from the viewpoint of reducing the environmental load.
[0020] Examples of water include distilled water, ion-exchanged water, ultrapure water, etc. Examples of water-soluble organic solvents include alcohols (methanol, ethanol, isopropanol, isobutanol, sec-butanol, tert-butanol, methyl cellosolve, ethyl cellosolve, ethylene glycol, glycerin, etc.), ethers (ethylene glycol dimethyl ether, 1,4-dioxane, tetrahydrofuran, etc.), ketones (acetone, methyl ethyl ketone), N,N-dimethylformamide, N,N-dimethylacetamide, dimethyl sulfoxide, etc.
[0021] <Dispersant> The dispersant is for dispersing carbon nanotubes. Examples of dispersants include ionic surfactants such as cationic surfactants, anionic surfactants, and amphoteric surfactants, nonionic surfactants, disaccharides such as sucrose, maltose, lactose, cellobiose, and trehalose, oligosaccharides such as cyclodextrin, steroid derivatives such as bile acid, cholesterol, and cholic acid, DNA, π-conjugated polymers, and phthalocyanine derivatives. Among these, steroid derivatives, especially bile acid, are preferred for the following reasons. Carbon nanotubes are hydrophobic, so when a steroid derivative is added as a dispersant, the hydrophobic group of the steroid derivative is bound to the surface of the carbon nanotube, and the carbon nanotube is pulled, making it easy for the carbon nanotube to be isolated and dispersed.
[0022] The content of the dispersant is preferably 10% by mass or more and 500% by mass or less relative to the content of the carbon nanotubes. If the content of the dispersant is 10% by mass or more, the carbon nanotubes are sufficiently dispersed, and if the content is 500% by mass or less, the process for removing the dispersant can be prevented from becoming complicated.
[0023] <Cellulose nanofiber> The ratio of the mass of cellulose nanofibers to the mass of carbon nanotubes in the carbon nanotube dispersion (mass of CNF / mass of CNT) is preferably 0.01 or more and 1.0 or less. If this ratio is 0.01 or more, the orientation of the carbon nanotubes can be easily controlled, and if it is 1.0 or less, the carbon nanotube structure obtained after the firing treatment can be prevented from becoming brittle. The lower limit of this ratio is preferably 0.03 or more, 0.05 or more, or 0.1 or more, and the upper limit is preferably 0.7 or less, 0.5 or less, or 0.3 or less.
[0024] The diameter of the cellulose nanofiber is preferably 3 nm or more and 80 nm or less. The diameter of the cellulose nanofiber can be measured using an atomic force microscope (AFM), and the diameter of 10 cellulose nanofibers is measured, and the arithmetic average value is defined as the diameter of the cellulose nanofiber.
[0025] The length of the cellulose nanofiber is preferably 0.1 μm or more and 100 μm or less. The length of the cellulose nanofiber can be measured using an atomic force microscope (AFM), where the lengths of 10 carbon nanotubes are actually measured, and the arithmetic average value is taken as the length of the cellulose nanofiber.
[0026] The ratio of length to diameter (length / diameter, aspect ratio) of the cellulose nanofiber is preferably 100 or more and 10,000 or less.
[0027] The cellulose nanofibers can have anionic functional groups. The cellulose nanofibers having anionic functional groups can be obtained by introducing anionic functional groups into the raw material during chemical treatment or into the physically defibrated material, and then further pulverizing (defibrating). In the pulverizing process, defibration is facilitated by the repulsive action of the anionic functional groups. Examples of the anionic functional groups include carboxylate groups, phosphate groups, sulfonate groups, sulfate groups, phosphite groups, xanthate groups (-OCSS-) and salts thereof. Examples of the cellulose nanofibers having anionic functional groups include oxidized cellulose nanofibers having a carboxyl group or a salt of a carboxyl group, phosphated cellulose nanofibers having a phosphate group or a salt of a phosphate group, sulfated cellulose nanofibers having a sulfate group or a salt of a sulfate group, phosphite cellulose nanofibers having a phosphite group or a salt of a phosphite group, and xanthated cellulose nanofibers having a xanthate group or a salt of a xanthate group. Examples of oxidized cellulose nanofibers include TEMPO oxidized cellulose nanofibers and carboxymethylated cellulose nanofibers.
[0028] <Monosaccharides> The monosaccharide is for orienting the carbon nanotubes in a specific direction. Examples of the monosaccharide include arabinose, ribose, xylose, glucose, mannose, galactose, fructose, sorbose, rhamnose, fucose, ribosaccharide, etc. Among these, glucose is preferred from the viewpoint of being able to better orient the carbon nanotubes.
[0029] The carbon nanotube dispersion can be obtained by heating a dispersion containing carbon nanotubes, a dispersion medium, a dispersant, cellulose nanofibers, and monosaccharides to a temperature of 120° C. to 180° C., or by heating a first dispersion containing cellulose nanofibers and monosaccharides to a temperature of 120° C. to 180° C., and then mixing the first dispersion with a second dispersion containing carbon nanotubes and a dispersion medium. By heating the dispersion containing cellulose nanofibers and monosaccharides to such a temperature, the monosaccharides become nanoparticles with a diameter of 5 nm to 80 nm, and these nanoparticles are formed on the surface of the cellulose nanofibers.
[0030] When the dispersion liquid and the first dispersion liquid are heated to a temperature of 120° C. or more and 180° C. or less, the heating is preferably carried out under a pressure of 0.2 MPa or more and 10 MPa or less. By treating under such high pressure, the hydrogen bonds between the cellulose nanofibers are shielded, and dispersed cellulose nanofibers are obtained.
[0031] The ratio of the mass of monosaccharides to the mass of cellulose nanofibers in the dispersion or the first dispersion before heating to the above temperature is 100 or more. If this ratio is 100 or more, the carbon nanotubes can be oriented in a specific direction, as described below. From the viewpoint of orienting the carbon nanotubes in a specific direction, the lower limit of this ratio is preferably 150 or more, 200 or more, 300 or more, or 500 or more. Furthermore, if the amount of monosaccharides is too large, it becomes difficult to remove the monosaccharides from the carbon nanotube structure, so this ratio is preferably 100,000 or less, 10,000 or less, or 2,000 or less.
[0032] After obtaining the carbon nanotube dispersion liquid, the carbon nanotube dispersion liquid 11 is supplied to a mold 12 as shown in Fig. 1(A). Next, the carbon nanotube dispersion liquid 11 is dried as shown in Fig. 1(B). This results in a solidified carbon nanotube dispersion liquid 13 (see Fig. 1(C)). The drying can be performed, for example, in an environment of 25°C or higher and 250°C or lower.
[0033] After obtaining the solidified material, the solidified material 13 is washed as shown in FIG. 1(C). Specifically, the solidified material 13 is first washed with a polar organic solvent such as alcohol. This makes it possible to remove dispersants, stabilizers, and the like used in dispersing the carbon nanotubes. Next, the solidified material 13 is washed with an acid. This makes it possible to remove impurities (e.g., catalysts) derived from the process in the manufacture of the carbon nanotubes. The concentration of the acid is preferably adjusted to 20% by mass or more. Examples of acids include hydrochloric acid and nitric acid. Finally, the carbon nanotube structure is washed with deionized water until it becomes neutral.
[0034] After washing the solidified material, the solidified material 13 is dried as shown in Fig. 2(A) . The drying can be performed, for example, in an environment of 25°C or higher and 250°C or lower.
[0035] After drying the solidified material 13, the solidified material is calcined at a temperature of 550°C to 1050°C in a nitrogen atmosphere as shown in Fig. 2(B) to carbonize it. As a result, the cellulose nanofibers, sugar compounds, etc. are carbonized to become amorphous carbon particles, which are released from the carbon nanotube solidified material by washing with subcritical water, thereby obtaining a high-purity carbon nanotube molding 14 (see Fig. 2(C)). The calcination time can be, for example, 30 minutes to 300 minutes.
[0036] 2(C), the carbon nanotube molded body 14 may be heated to a temperature of 650° C. or more and 2700° C. or less in a carbon dioxide atmosphere to activate the carbon nanotube molded body 14. The heating time may be, for example, 30 minutes to 300 minutes.
[0037] <<<Carbon nanotube molded body>>> The carbon nanotube molded body obtained by the above-mentioned production method has a high density and a large specific surface area. 3 and the specific surface area is 500m or more. 2 / g or more. The density of the carbon nanotube molded body can be obtained by measuring the weight and volume in an environment with a temperature of 23°C to 27°C and a relative humidity of 30% to 70%, and the arithmetic average value of the densities of 10 samples taken from the carbon nanotube molded body is defined as the density of the carbon nanotube molded body. The specific surface area of the carbon nanotube molded body can be obtained based on the BET method, and the arithmetic average value of the specific surface areas of three samples taken from the carbon nanotube molded body is defined as the specific surface area of the carbon nanotube molded body.
[0038] The lower limit of the density of the carbon nanotube compact is 0.60 g / cm 3 More than 0.62g / cm 3 More than 0.63g / cm 3 or more than 0.64g / cm 3The upper limit is preferably 0.80 g / cm from the viewpoint of the difficulty of producing a carbon nanotube molded product. 3 Below, 0.70g / cm 3 or less than 0.68g / cm 3 It may be the following:
[0039] The lower limit of the specific surface area of the carbon nanotube molded body is 600 m 2 / g or more, 650m 2 / g or more, 700m 2 / g or more, or 750m 2 / g or more, and the upper limit is 1500 m 2 / g or less, 1000m 2 / g or less, or 800m 2 / g or less.
[0040] The carbon content in the carbon nanotube molded product is preferably 55% by mass or more. If the carbon content is 55% by mass or more, a carbon nanotube molded product with few impurities can be obtained. The lower limit of the content is more preferably 65% by mass or more, 85% by mass or more, or 95% by mass or more, but the upper limit may be 95% by mass or less, 80% by mass or less, or 60% by mass or less from the viewpoint of the time and cost of the purification process. The carbon content can be measured by elemental analysis using an energy dispersive X-ray spectrometer (product name: "JED-2300T Energy Dispersive X-ray Spectrometer", manufactured by JEOL Ltd.).
[0041] The carbon nanotube molded body preferably has a tensile strength of 20 MPa or more and an elastic modulus of 1000 MPa or more. The tensile strength and elastic modulus can be measured using a tensile tester (product name "Tensile Tester QC-536M1", manufactured by Comtec Co., Ltd.) in an environment of a temperature of -60°C or more and 300°C or less and a relative humidity of 70% or less.
[0042] It is preferable that the carbon nanotube molded body does not crack when subjected to a bending test in which the carbon nanotube molded body is bent 1 million times. This allows for excellent flexibility. Generally, metal molded bodies break after about 100,000 times. The bending test can be performed using a bending tester (product name "DeMacha Bending Tester", manufactured by Yasuda Seiki Seisakusho Co., Ltd.) in an environment with a temperature of 23°C to 27°C and a relative humidity of 30% to 70%.
[0043] The surface resistance of the carbon nanotube molded body is preferably 10 Ω / □ or less. The surface resistance can be measured with a contact resistivity meter (product name "Loresta GP MCP-T610", manufactured by Mitsubishi Chemical Analytech Co., Ltd., probe: ASP) in an environment with a temperature of 23°C to 27°C and a relative humidity of 30% to 70%, and the arithmetic average of the surface resistance values measured at 10 points is defined as the surface resistance of the carbon nanotube molded body.
[0044] The shape of the carbon nanotube molded body is not particularly limited, and may be, for example, a sheet, a cylinder, or a columnar shape.
[0045] The uses of the carbon nanotube molded body are not particularly limited, but the carbon nanotube molded body can be used, for example, as an electromagnetic wave shield, an electrode for a capacitor (particularly, a large-capacity capacitor with a cell capacity of 80 F / G), a catalyst for the oxygen evolution reaction (OER), the hydrogen evolution reaction (HER), and the oxygen reduction reaction (ORR), a gas storage material, a gas barrier material, a separator, a heating material, and electrolytic plating.
[0046] The cellulose nanofibers have strong hydrogen bonds and tend to form aggregates. Therefore, the carbon nanotubes cannot enter between the cellulose nanofibers, and the carbon nanotubes are difficult to orient. In contrast, according to this embodiment, the ratio of the mass of monosaccharides to the mass of cellulose nanofibers in the carbon nanotube dispersion is set to 100 or more, and the dispersion containing the cellulose nanofibers and the monosaccharides is heated to a temperature of 120° C. to 180° C., whereby the monosaccharides become nanoparticles having a diameter of 5 nm to 80 nm, and these nanoparticles are formed on the surfaces of the cellulose nanofibers, thereby breaking the hydrogen bonds between the cellulose nanofibers and loosening the cellulose nanofiber aggregates. Therefore, the addition of monosaccharides to the cellulose nanofibers and the nanoparticleization of the monosaccharides loosens the cellulose nanofibers, and the carbon nanotubes can be allowed to enter between the cellulose nanofibers, so that the carbon nanotubes can be oriented along the longitudinal direction of the cellulose nanofibers. This makes it possible to suppress the carbon nanotubes from being present as bundles, and therefore the specific surface area can be increased. In addition, since the carbon nanotubes are oriented, the mechanical strength (for example, tensile strength and bending property) can be improved.
[0047] Furthermore, since the carbon nanotube molding is formed using a carbon nanotube dispersion liquid, the density of the carbon nanotube molding can be increased more than when the carbon nanotube molding is formed using a CVD method. EXAMPLES
[0048] In order to explain the present invention in detail, the following examples are given, but the present invention is not limited to these examples. Fig. 3 is a scanning electron microscope photograph of the carbon nanotube molded article according to Example 1.
[0049] <Example 1> First, a carbon nanotube dispersion was obtained. The carbon nanotube dispersion was obtained by mixing 100 ml of the first dispersion and 100 ml of the second dispersion. The first dispersion contained 0.1% by mass of TEMPO-oxidized cellulose nanofibers, 20% by mass of glucose, and water as a dispersion medium. That is, in the first dispersion, the ratio of the mass of glucose to the mass of TEMPO-oxidized cellulose nanofibers was 200. Note that TEMPO is 2,2,6,6-tetramethylpiperidine-1-oxyl. The first dispersion was treated for 6 hours at a temperature of 120°C and a pressure of 0.2 MPa using a Teflon (registered trademark) reaction vessel capable of withstanding high temperatures and high pressures, and then allowed to cool to room temperature before use. The second dispersion contained 0.75 mass % single-walled carbon nanotubes (product name "TUBALL", manufactured by OCSIAL), water as a dispersion medium, and 1.5 mass % polyvinylpyrrolidone and 3.0 mass % sodium cholate as dispersants.
[0050] After obtaining the carbon nanotube dispersion liquid, the carbon nanotube dispersion liquid was supplied to a container and dried in an environment of 200° C. to obtain a solidified material of carbon nanotubes.
[0051] After obtaining the solidified material, the solidified material was washed with ethanol three times for 12 hours and dried in air at 35° C. Then, the solidified material was washed with concentrated nitric acid twice for 8 hours, and then washed with deionized water several times until the pH reached 7. Then, the solidified material was dried in air at 200° C.
[0052] The solidified material was then stabilized at 280°C for 90 minutes under a nitrogen atmosphere while supplying nitrogen at a rate of 1000 ml / min. The solidified material was then fired at 900°C for 120 minutes while supplying nitrogen at a rate of 1000 ml / min, and carbonized. As a result, a carbon nanotube molded product was obtained.
[0053] After obtaining the carbon nanotube sheet, the carbon nanotube sheet was stabilized at 280°C for 90 minutes under a nitrogen atmosphere while supplying nitrogen at a rate of 1000ml / min. Thereafter, the solidified material was heated to 900°C under a nitrogen atmosphere while supplying nitrogen at a rate of 1000ml / min, and was maintained at 900°C for 60 minutes under a carbon dioxide atmosphere while supplying carbon dioxide at a rate of 350ml / min, thereby activating the carbon nanotube sheet. As a result, a carbon nanotube sheet having a thickness of 15 μm according to Example 1 was obtained.
[0054] <Example 2> In Example 2, a carbon nanotube sheet was obtained in the same manner as in Example 1, except that the ratio of the mass of glucose to the mass of TEMPO-oxidized cellulose nanofibers in the first dispersion before heating was set to 150.
[0055] <Example 3> In Example 3, a carbon nanotube sheet was obtained in the same manner as in Example 1, except that the ratio of the mass of glucose to the mass of TEMPO-oxidized cellulose nanofibers in the first dispersion before heating was set to 100.
[0056] <Comparative Example 1> In Comparative Example 1, a carbon nanotube sheet was obtained in the same manner as in Example 1, except that the ratio of the mass of glucose to the mass of TEMPO-oxidized cellulose nanofibers in the first dispersion before heating was set to 10.
[0057] <Comparative Example 2> In Comparative Example 2, a carbon nanotube sheet was obtained in the same manner as in Example 1, except that the ratio of the mass of glucose to the mass of TEMPO-oxidized cellulose nanofibers in the first dispersion before heating was set to 1.
[0058] <Comparative Example 3> In Comparative Example 3, a carbon nanotube sheet was obtained in the same manner as in Example 1, except that no glucose was added.
[0059] <Density measurement> The density of the carbon nanotube sheet was measured in the carbon nanotube sheets according to Examples 1 to 3 and Comparative Examples 1 to 3. Specifically, first, 10 samples were taken from the carbon nanotube sheet. Then, the density of the sample was calculated by measuring the weight and volume of each sample, and the arithmetic average value of the densities of the 10 samples was determined as the density of the carbon nanotube sheet.
[0060] <Specific surface area measurement> The specific surface area of the carbon nanotube sheet was measured for the carbon nanotube sheets according to Examples 1 to 3 and Comparative Examples 1 to 3. Specifically, first, three samples were taken from the carbon nanotube sheet. Then, the specific surface area of each sample was determined based on the BET method, and the arithmetic average value of the specific surface areas of the three samples was determined as the specific surface area of the carbon nanotube sheet.
[0061] <Carbon content> The carbon content was measured for the carbon nanotube sheets according to Examples 1 to 3 and Comparative Examples 1 to 3. Specifically, the carbon content was measured by elemental analysis using an energy dispersive X-ray spectrometer (EDX, product name "JED-2300T Energy Dispersive X-ray Spectrometer", manufactured by JEOL Ltd.).
[0062] <Surface resistance measurement> The surface resistance of the carbon nanotube sheet according to Examples 1 to 3 and Comparative Examples 1 to 3 was measured. Specifically, the surface resistance of the carbon nanotube sheet was measured using a contact resistivity meter (product name "Loresta GP MCP-T610", manufactured by Mitsubishi Chemical Analytech Co., Ltd., probe: ASP) in an environment of a temperature of 25°C and a relative humidity of 50%. The average value of the values measured at 10 points was taken as the surface resistance.
[0063] <Measurement of tensile strength and tensile modulus> The tensile strength and tensile modulus of the carbon nanotube sheets according to Examples 1 to 3 and Comparative Examples 1 to 3 were measured. Specifically, six samples were taken from the carbon nanotube sheet. Then, the tensile strength and tensile modulus of each sample were measured using a tensile tester (product name "tensile tester QC-536M1", manufactured by Comtec Co., Ltd.). The tensile strength was measured at temperatures of -60°C, 23°C, and 300°C, and in an environment with a relative humidity of 70% or less. The tensile modulus was measured in an environment with a temperature of 25°C and a relative humidity of 50%. The arithmetic mean value of the tensile strengths of the six samples was taken as the tensile strength of the carbon nanotube sheet, and the arithmetic mean value of the tensile modulus of the six samples was taken as the tensile modulus of the carbon nanotube sheet.
[0064] <Bending evaluation> A bending test was conducted on the carbon nanotube sheets according to Examples 1 to 3 and Comparative Examples 1 to 3 by bending the carbon nanotube sheets 1 million times to evaluate whether cracks occurred in the carbon nanotube sheets. Specifically, first, samples were taken from the carbon nanotube sheets. Then, a bending test was conducted on each sample by bending the sample 1 million times using a bending tester (product name "DeMacha bending tester", manufactured by Yasuda Seiki Seisakusho Co., Ltd.) in an environment of a temperature of 25°C and a relative humidity of 50%. The evaluation criteria were as follows: A: Even after being folded a million times, the carbon nanotube sheet did not crack. B: After being bent 10,000 times, cracks appeared in the carbon nanotube sheet. C: After being bent 3,000 times, the carbon nanotube sheet started to crack. D: After 500 folds, cracks were generated in the carbon nanotube sheet.
[0065] The results are shown in Table 1 below. [Table 1]
[0066] The carbon nanotube sheets according to Comparative Examples 1 to 3 had low density and small specific surface area because the ratio of the mass of glucose to the mass of TEMPO oxidized cellulose nanofibers in the first dispersion liquid before heating was less than 100. In contrast, the carbon nanotube sheets according to Examples 1 to 3 had high density and large specific surface area because the ratio of the mass of glucose to the mass of TEMPO oxidized cellulose nanofibers in the carbon nanotube dispersion liquid was 100 or more.
[0067] The carbon nanotube sheet according to Example 1 was photographed at a magnification of 10,000 times using a scanning electron microscope (product name "JSM-IT100 type", manufactured by JEOL Ltd.), and the photograph shown in Fig. 3 was obtained. From Fig. 3, it was confirmed that the carbon nanotubes in the carbon nanotube sheet according to Example 1 were oriented in a specific direction. [Explanation of symbols]
[0068] 11…Carbon nanotube dispersion liquid 12…Type 13...Solidified material 14...Carbon nanotube molding
Claims
1. A method for producing a carbon nanotube molded body containing carbon nanotubes, comprising the steps of: Obtaining a carbon nanotube dispersion liquid containing carbon nanotubes, cellulose nanofibers, monosaccharides, and a dispersion medium; supplying the carbon nanotube dispersion liquid into a mold and drying the same to obtain a solidified product of the carbon nanotube dispersion liquid; and burning the solidified material to carbonize the cellulose nanofibers. the step of obtaining the carbon nanotube dispersion includes a step of heating a dispersion containing the carbon nanotubes, the cellulose nanofibers, the monosaccharides, and the dispersion medium to a temperature of 120° C. or higher and 180° C. or lower, or a step of heating a first dispersion containing the cellulose nanofibers and the monosaccharides to a temperature of 120° C. or higher and 180° C. or lower, and then mixing the first dispersion with a second dispersion containing the carbon nanotubes and the dispersion medium; The production method, wherein the ratio of the mass of the monosaccharides to the mass of the cellulose nanofibers in the dispersion liquid or the first dispersion liquid before the heating is 100 or more.
2. The method according to claim 1 , wherein the heating is carried out under a pressure of 0.2 MPa or more and 10 MPa or less.
3. A carbon nanotube molding containing carbon nanotubes, The density of the carbon nanotube molded body is 0.55 g / cm 3 That's all. The specific surface area of the carbon nanotube molded body is 500 m 2 / g or more, A carbon nanotube molding, wherein the carbon nanotubes are oriented in a specific direction.
4. 4. The carbon nanotube molded body according to claim 3, wherein the carbon content in the carbon nanotube molded body is 55 mass % or more.
5. The carbon nanotube molded body according to claim 3 , wherein the carbon nanotube molded body is a carbon nanotube sheet.
Citation Information
Patent Citations
Method for dispersing carbon nanotube in water
JP2008230935A
High density carbon nanotube aggregate and method of manufacturing the same
JP2010083722A
Carbon nanomaterial dispersion
JP2012240875A
Composition containing microfibrillated cellulose and method for producing the composition
JP2013527876A
Carbon aggregate assemblies and their applications
JP2014529559A